Local collection, reaction and analysis with theta pipette emitters. Issue 9 (31st March 2017) - Saha-Shah, Anumita; Karty, Jonathan A.; Baker, Lane A.
Abstract : A mobile nanofluidic device based on theta pipettes was developed for "collect-react-analyze" measurements of small volumes of a sample collected locally from biological samples. Abstract : A mobile nanofluidic device based on theta pipettes was developed for "collect-react-analyze" measurements of small volumes of a sample collected locally from biological samples. Specifically, we demonstrate execution of local reactions inside single cells and on Pseudomonas aeruginosa biofilms for targeted analysis of metabolites. Nanoliter volumes of the sample, post-reaction, were delivered to a mass spectrometer via electrospray ionization (ESI) for chemical analysis. A new strategy was developed where the additional barrel of a theta pipette was utilized both to enable chemical manipulations after sample collection and to electrospray the nanoliter sample volumes collected directly from the pipette tip. This strategy proved a robust method for ESI from nanometer sized tips without clogging or degradation of the emitter and obviated the need to coat glass pipettes with a conductive metal coating. Chemical reactions investigated include acid catalyzed degradation of oligosaccharides inside the pipette tip to increase the detection sensitivity of minor metabolites found in Allium cepa cells. Additionally, phenylboronic acid complexation of carbohydrates from single cells and liposaccharides from biofilms was also performed inside the pipette tip for selective detection of carbohydrates and liposaccharides with cis -diols.